Practicing COVID-19 Public Health Measures Is Associated With Anxiety and Depression in Undergraduate University Students - Holladay, Kelley; Lardier, David; Amorim, Fabiano T.; Zuhl, Micah; Coakley, Kathryn E. (Frontiers in Public Health, 2022)
Background: COVID-19 has affected mental health globally, increasing depression and anxiety. This study examined relationships between practicing COVID-19-related public health measures and depression and anxiety in young adult students. Methods: A sample of 755 undergraduate students 18-25 years of age at a large public university completed a cross-sectional survey in fall 2020 during the pandemic (response rate=18.9%). The survey included demographic questions, anxiety and depression screeners (GAD-7 and PHQ-9), and questions on practicing public health measures (stay-at-home orders, quarantining, social distancing, etc.) since March 2020. Multivariate logistic regression was utilized to calculated adjusted odds between practicing public health measures and anxiety and depression. Results: The majority of respondents reported practicing public health measures; however, 53% experienced anxiety (GAD-7 score>10) and 57% experienced depression (PHQ-9 score>10) in the two weeks prior to completing the survey. Participants who quarantined had significantly higher odds of anxiety (AOR=1.44; 95% CL 1.07, 1.96) and depression (OR=1.77; 95% CL 1.30, 2.41) than those who did not. Participants who self-isolated also had significantly higher odds of anxiety (OR=1.53; 95% CL 1.13, 2.08) and depression (OR=1.87; 95% CL 1.37, 2.56) compared to those who did not. Moving/changing living situations in response to the pandemic also increased odds of depression (OR=1.86; 95% CL 1.33, 2.60). Conclusion: Young adult undergraduate students experienced a high prevalence of anxiety and depression. Quarantining, self-isolating, and moving/changing living situations increased odds of anxiety and/or depression. The public health measures necessary for COVID-19 control and prevention may adversely affected mental health.